Navigating Western and Islamic Cultural Values in English Education: A Narrative Case Study of Teachers at International Islamic Boarding School - Farah, Rafika Rabba (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
Globalization has urged many students across the globe to be proficient in achieving academic success and career, including those Muslim students studying in boarding school settings. Scholars have debated the intertwin between English and Western culture. However, empirical studies that discusses the relationship between English and Islam is not well explored. This study aims to provide new insights into this complex matter, particularly on how teachers’ beliefs and experiences in English teaching at Islamic-affiliated schools is delivered. The method applied in this present research is a qualitative design, particularly using a narrative case study. Applying the design, this study explores the participants’ personal stories that are unique and rich with the relationship of social, cultural, and political measurement in reshaping their experiences. Thus, to achieve the answers, four teachers’ belief and their pedagogical practices in teaching English to students at the International Islamic Boarding School (IIBS) in Malang Region Indonesia were investigated through a semi-structured interview. Results reveal that English teaching at the schools was contextualized to the school vision and value which is to instill Islamic principles; teachers believe English has conflicting norms to Muslim students’ values; English activities are massively exposed to the Muslim students through several English enrichment programs; and English is prepared for students to be both competent in their future professional works and to spread the message of Islam. This finding has shed light that English teaching at Islamic-based schools can be contextualized to students’ needs and school cultures. Thus, this study contributes to explaining how teachers’ belief shapes their English teaching practices through designing Islamic pedagogy for their Muslim students.